Miscellaneous
Misc 2
Misc 3
Misc 4 Important
Misc 5
Misc 6
Misc 7 Important
Misc 8
Misc 9
Misc 10 Important You are here
Misc 11 (i) Important
Misc 11 (ii)
Misc 12 Important
Misc 13
Misc 14 Important
Misc 15 Important
Misc 16
Misc 17 Important
Misc 18 Important
Question 1 Deleted for CBSE Board 2025 Exams
Question 2 Deleted for CBSE Board 2025 Exams
Question 3 Important Deleted for CBSE Board 2025 Exams
Question 4 Deleted for CBSE Board 2025 Exams
Question 5 Deleted for CBSE Board 2025 Exams
Question 6 Important Deleted for CBSE Board 2025 Exams
Question 7 Deleted for CBSE Board 2025 Exams
Question 8 Deleted for CBSE Board 2025 Exams
Question 9 Important Deleted for CBSE Board 2025 Exams
Question 10 Deleted for CBSE Board 2025 Exams
Question 11 Important Deleted for CBSE Board 2025 Exams
Question 12 Deleted for CBSE Board 2025 Exams
Question 13 Important Deleted for CBSE Board 2025 Exams
Question 14 Deleted for CBSE Board 2025 Exams
Miscellaneous
Last updated at April 16, 2024 by Teachoo
Misc 10 The ratio of the A.M and G.M. of two positive numbers a and b, is m: n. Show that a : b = (m + ( ^2 ^2 )) : (m ( ^2 ^2 ) ) Introduction Componendo dividendo If / = / Applying componendo dividendo ( + )/( ) = ( + )/( ) Eg: Taking 1/2 = 4/8 (1+ 2)/(1 2) = (4 + 8)/(4 8) 3/( 1) = 12/( 4) -3 = -3 Misc 19 The ratio of the A.M and G.M. of two positive numbers a and b, is m: n. Show that a : b = (m + ( ^2 ^2 )) : (m ( ^2 ^2 ) ) Here, the two numbers be a and b. Arithmetic Mean =AM= (a+b)/2 & Geometric Mean=GM= ab According to the question, AM/( GM" " ) = / ( + )/(2 " " ) = / Applying componendo dividendo ( + +2 )/( + 2 ) = ( + )/( ) (( )2+( )2+2( ))/(( )2+( )2 2( ) ) =( + )/( ) Using (x + y)2 = x2 + y2 + 2xy (x - y)2 = x2 + y2 - 2xy ( + )2/( )2 = ( + )/( ) (( + )/( ))^2 = ( + )/( ) ( + )/( ) = (( + )/( )) ( + )/( ) = ( + )/( ( ) ) Applying componendo dividendo (( + ) + ( ))/(( + ) ( ) ) = ( ( + ) + ( ))/( ( + ) ( )) (2 )/(2 ) = ( ( + ) + ( ))/( ( + ) ( )) / = ( ( + ) + ( ))/( ( + ) ( )) Squaring both sides ( / )^2 = (( ( + ) + ( ))/( ( + ) ( )))^2 ( )^2/( )^2 = ( ( + ) + ( ))^2/( ( + ) ( ))^2 Using (x + y)2 = x2 + y2 + 2xy (x - y)2 = x2 + y2 - 2xy / = (( ( + ) )^2+( ( ) )^2+ 2( ( + ))( ( )))/(( ( + ) )^2+( ( ) )^2 2( ( + ))( ( )) ) / = ( + + + 2 (( + )( ) ))/( + + 2 (( + )( ) )) / = ( + + + 2 (( ^2 ^2 ) ))/( + + 2 (( ^2 ^2 ) )) / = (2 + 2 (( ^2 ^2 ) ))/(2 2 (( ^2 ^2 ) )) / = 2( + (( ^2 ^2 ) ))/2( (( ^2 ^2 ) )) / = ( + (( ^2 ^2 ) ))/( (( ^2 ^2 ) )) Thus, a : b = (m + ( ^2 ^2 )) : (m ( ^2 ^2 ) ) Hence proved